Cybernetic Modelling in the General Classification of Modelling Types - Kunčinas, Algirdas (Problemos, 1976)
In its first part the article deals with different classification of modelling types. In the process of analysis it is proved that classification systems created to answer the needs of particular branches of science do not meet the requirements of gnoseological analysis. In the second part of the article the author shows that, on the one hand, cybernetic modelling cannot be identified with any kind of modelling singled out in these systems. On the other hand, cybernetic modelling cannot be singled out of these systems as an independent type. Therefore, an attempt is made to investigate what types of modelling in these systems are most widely applied in cybernetic modelling, which of them and for what reason are the most effective ones.